Flöhe aus dem Mittelmeergebiet (Siphonaptera). IV. Sardinien, Korsika und benachbarte kleine Inseln. - Peus, Fritz (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There are presented the author’s results on his investigations of fleas collected by H. Kahmann, Munich from little mammals during several collecting trips to Sardinia, Corsica and some small neighbouring islands in 1952-1955. Nomenclatural Acts corsus Peus, 1963 (Ctenophthalmus agyrtes), sspec. n.